CREATIVE SPACE BAGI PENYANDANG GANGGUAN MENTAL DI BANJARBARU - Rachfa, Adhinda SafiraFaizatur; Muchammad, Bani Noor (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
Mental disorders are one of the social phenomena whose number is increasing every year. The increase in people with mental disorders is not accompanied by an increase in mental health facilities in Indonesia, especially in Banjarbaru. Creative Space for People with Mental Disorders in Banjarbaru is designed to be an alternative means of therapy and counseling for people with mental disorders through creative activities, with a behavior setting method that makes behavior the main focus in its design. And the concept of "blank canvas" which has four development points, namely sequence, expressive, collaborative, and flexibility. The existence of this creative space is also expected to be able to change the paradigm of society regarding the issues of mental disorders which are still bad. Through a design that puts forward the concept of sequences through the use of ramps and corridors that are able to provide a space experience for visitors, where the space experience can make visitors more expressive so that designs are made expressive through collaborative and flexible activities and designs through interiors and the use of furniture. on the plan. With this creative space, it is also hoped that the rigid impression that exists in mental health facilities will disappear, and can generate creative activities for the Banjarbaru community, especially for people with mental disorders.